Biodegradability of Cellulose Fibers, Films, and Particles: A Review - Martin A. Hubbe; Jesse S. Daystar; Richard A. Venditti; Joel J. Pawlak; Marielis C. Zambrano; Morton Barlaz; Mary Ankeny; Steven Pires (BioResources)
Cellulose fibers are an abundant material that is well known for its biodegradability. Various forms of cellulose, such as cotton, paper pulp fibers, and microcrystalline cellulose can be regarded as benchmarks for biodegradability, when comparing other materials. However, as revealed by the literature, broad ranges of time and extent of biodegradation have been reported for cellulose. These large ranges can be attributed not only to environmental factors but also to the presence of lignin, the degree and perfection of crystallinity, the size and density of the physical specimens, and chemical modifications to the cellulose, if any. Studies also have shown differences in biodegradability associated with the selection of test methods. Although cellulose is subject to well-known enzyme-promoted mechanisms of biodegradation, the evolution of plant materials has favored development of some resistance to decay, i.e. recalcitrance. Cellulosic materials are clearly less biodegradable than starch. However, they are more biodegradable than various synthetic or bio-based plastics, as well as some cellulose derivatives, which persist in ocean water or soils for very long periods. This review indicates that cellulose biodegradability, while generally rapid and natural, has a rate and extent that depends on a complex and sometimes subtle set of environmental and chemical factors.